2013
DOI: 10.3390/min3030318
|View full text |Cite
|
Sign up to set email alerts
|

Potentiostatically Poised Electrodes Mimic Iron Oxide and Interact with Soil Microbial Communities to Alter the Biogeochemistry of Arctic Peat Soils

Abstract: Dissimilatory metal-reducing bacteria are ubiquitous in soils worldwide, possess the ability to transfer electrons outside of their cell membranes, and are capable of respiring with various metal oxides. Reduction of iron oxides is one of the more energetically favorable forms of anaerobic respiration, with a higher energy yield than both sulfate reduction and methanogenesis. As such, this process has significant implications for soil carbon balances, especially in the saturated, carbon-rich soils of the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 53 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…These BESs produce power in microbial fuel cells (MFCs; He et al, 2005 ; Fornero et al, 2010a , b ; Rosenbaum et al, 2011b ); produce chemical products in microbial electrolysis cells ( Rozendal et al, 2009 ; Villano et al, 2010 ; Cheng and Logan, 2011 ; Cusick et al, 2011 ; Rosenbaum et al, 2011a ); remediate pollutants ( Gregory and Lovley, 2005 ; Strycharz et al, 2010 ; Morris and Jin, 2012 ); sense environmental and chemical parameters ( Chang et al, 2005 ; Kumlanghan et al, 2007 ); and produce logic gates in biocomputing devices ( Li et al, 2011 ; TerAvest et al, 2011 ). In the environment, potentiostatically poised electrodes (i.e., electrodes held at a constant electrical potential using an electrical device called a potentiostat), can mimic iron(III)- and humic substance-compounds and act as the terminal electron acceptor for dissimilatory metal-reducing bacteria ( Williams et al, 2010 ; Zhang et al, 2010 ; Friedman et al, 2012 , 2013 ). The advantage of using an electrode instead of, for example, iron(III) is that the electrode can act as an inexhaustible terminal electron acceptor, which can be set precisely to the potential of interest without any other chemical interactions with the community.…”
Section: Introductionmentioning
confidence: 99%
“…These BESs produce power in microbial fuel cells (MFCs; He et al, 2005 ; Fornero et al, 2010a , b ; Rosenbaum et al, 2011b ); produce chemical products in microbial electrolysis cells ( Rozendal et al, 2009 ; Villano et al, 2010 ; Cheng and Logan, 2011 ; Cusick et al, 2011 ; Rosenbaum et al, 2011a ); remediate pollutants ( Gregory and Lovley, 2005 ; Strycharz et al, 2010 ; Morris and Jin, 2012 ); sense environmental and chemical parameters ( Chang et al, 2005 ; Kumlanghan et al, 2007 ); and produce logic gates in biocomputing devices ( Li et al, 2011 ; TerAvest et al, 2011 ). In the environment, potentiostatically poised electrodes (i.e., electrodes held at a constant electrical potential using an electrical device called a potentiostat), can mimic iron(III)- and humic substance-compounds and act as the terminal electron acceptor for dissimilatory metal-reducing bacteria ( Williams et al, 2010 ; Zhang et al, 2010 ; Friedman et al, 2012 , 2013 ). The advantage of using an electrode instead of, for example, iron(III) is that the electrode can act as an inexhaustible terminal electron acceptor, which can be set precisely to the potential of interest without any other chemical interactions with the community.…”
Section: Introductionmentioning
confidence: 99%
“…The anoxic basins representative of the North Slope landscape near Utqiaġvik are characterized by Fe-driven soil respiration [40,52,77]. We hypothesize that high native Fe concentrations and the importance of Fe-reduction respiration in these wetland soils favor AOM energetically linked with Fe-reduction, as has been seen in some high-Fe freshwater systems [22,24,82].…”
Section: Drivers and Stressorsmentioning
confidence: 90%
“…However, recent studies using 16s rRNA gene sequences in this landscape have shown the ubiquity of methanogen communities and a convergence in microbial composition within the active layer, regardless of basin age class [76]. Therefore, differences in microbial communities between age classes in this ecosystem appear to be more subtle than changes associated with soil depth and microtopography [40,71,77]. Utqiaġvik soil isolates related to methanogens capable of Fe(III)-reduction were detected [63], namely the Methanosarcina, Methanobacterium palustre, and Methanococcus clades ( Figure 2), grouping closely amongst ANME groups 2 and 3, with greater separation from the ANME group 1.…”
Section: Aom-associated Microbes and Genesmentioning
confidence: 97%
See 2 more Smart Citations